PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIB UPT SPF SD INPRES BONTOMANAI - Klara Kambong; Husnaeni; Amal Akbar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is a classroom action research (PTK) carried out at UPT SPF SDI Bontomanai with the aim of improving student learning outcomes using the Problem Based Learning (PBL) model in science subjects. The subjects in this study are class VIB students total 20 students. The instrument in this study is in the form of multiple-choice questions total 20 numbers. The data analysis technique in this study consists of quantitative data analysis. The results of this study show that there is an increase in student learning outcomes in each cycle using the Problem Based Learning (PBL) model. In the pre-cycle, an average score of 60,25 was obtained with a completion percentage of 50% and in Cycle I an average score of 66,75 with a completion percentage of 65% and in Cycle II an average score of 76,25with a completion percentage of 80%. This data shows that the application of the Problem Based Learning model has an effect on the learning outcomes of students in science subjects